Interactive drilling for fast track oilfield development proceedings of the seminar held in Rueil-Malmaison, November 9, 1999 - Lecourtier, Jacqueline (Editions Technip, 2001)
Annotation The proceedings from the November 1999 Rueil-Mamaison conference feature seven papers and a synthesis of round table discussions. They address strategies for the development of oil fields, interactive procedures, and measurement techniques. Specific papers discuss well data acquisition strategies, geosteering opportunities, improved drilling performance, and wellbore stability. Contributors include specialists from Agip, BP, Amoco, Elf, Geoservices, Statoil, and TotalFina. c. Book News Inc.
Keywords: Oil well drilling -- Congresses.; elektronické knihy; electronic books